Factors Affecting Unmet Need for Presbyopia Correction Among School Teachers in Debre Tabor Town, Northwest Ethiopia - Yalew AB; Alemu HW; Alemayehu AM (Clinical Optometry, 2023)
Amsalu Belete Yalew,1,* Haile Woretaw Alemu,2,* Abiy Maru Alemayehu2,* 1Department of Ophthalmology and Optometry, School of Medicine, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 2Department of Optometry, School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia*These authors contributed equally to this workCorrespondence: Abiy Maru Alemayehu, Email abidanmaru03@gmail.comBackground: Uncorrected presbyopia is the leading cause of near visual impairment among working-age adults in the world. In Ethiopia, there was limited evidence on the magnitude of uncorrected presbyopia and its associated factors among school teachers. Therefore, this study aimed to determine the magnitude of untreated presbyopia and its associated factors among school teachers in Debre Tabor town, Northwest Ethiopia.Methods: An institution-based cross-sectional study was conducted on 448 school teachers at Debre Tabor town using a simple random sampling technique. The data were collected using a face-to-face interview and a comprehensive ocular examination. A binary multivariable logistic regression model was conducted to identify associated factors of the uncorrected presbyopia.Results: Generally, the prevalence of uncorrected presbyopia among school teachers was 63.62% (95% CI: 59.2– 67.9). Age (35– 45) (AOR: 4.56, 95% CI: 1.74, 11.91), female gender (AOR: 3.03, 95% CI: 1.75, 5.26), unaware of presbyopia (AOR: 2.35, 95% CI: 1.30, 4.25), unaware of refraction site (AOR: 4.21, 95% CI: 2.42, 7.33), no eye checkup history (AOR: 2.76, 95% CI: 1.52, 5.01), and no family history of spectacle use (AOR: 2.61, 95% 4.67) were significantly associated with uncorrected presbyopia.Conclusion: In the current study, the magnitude of uncorrected presbyopia was high. Age below 45 years, female gender, lack of awareness of presbyopia and refraction site, lack of history of eye checkups, and family spectacle use were significantly associated with uncorrected presbyopia. The early correction of presbyopia, health education on presbyopia, and the provision of affordable spectacle corrections for school teachers were recommended.Keywords: Debre Tabor, Ethiopia, magnitude, presbyopia